2010
DOI: 10.1063/1.3306449
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of Ar between two identical parallel semi-infinite walls

Abstract: The confinement of Ar in planar slits of two identical parallel semi-infinite walls of alkali metals, alkaline-earth metal Mg, and CO 2 is investigated within the framework of the density functional theory. It is assumed that ͑1͒ the fluid atoms interact via a recently proposed effective attractive pair potential with strength, f f , which reproduces the experimental data of the surface tension of the liquid-vapor interface at the bulk coexistence curve, and ͑2͒ the adsorption on the walls is described by ab i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…for only one side (the n-th). Hence, the shape of U(r, ς) ∩ A is determined by the one dimensional position variable r (1) = d(r, ∂A 1,n ) = z, and then, g(r) = g 1 (r) = g 1 r (1) = g 1 (z). vertex (the n-th).…”
Section: Integration Over a Polytope-shaped Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…for only one side (the n-th). Hence, the shape of U(r, ς) ∩ A is determined by the one dimensional position variable r (1) = d(r, ∂A 1,n ) = z, and then, g(r) = g 1 (r) = g 1 r (1) = g 1 (z). vertex (the n-th).…”
Section: Integration Over a Polytope-shaped Domainmentioning
confidence: 99%
“…Besides, from Corollary 3 and using Eqs. (1) to (7) we obtain the explicit form of Ω and P W in terms of X. The expressions for S, U and the EOS in this GCE are easily found by replacing F with Ω in Eqs.…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent simultaneous study of wetting and filling we found some evidence for a correspondence between T cpw of a single PW line obtained in the case of one wall adsorption and T sb determined for the disappearance of SSB in slits. 10,12 Moreover, Rżysko et al 15 have also suggested that the SSB is a result of the first-order nature of the transition. If the transition were of the second order, SSB would not occur.…”
mentioning
confidence: 99%
“…In most of the studies, a Canonical Ensemble (CE) statistics was applied to examine filling of closed slits with classical gases. [6][7][8][9][10][11][12] Recently, Berim and Ruckenstein 13 have also investigated the occurrence of SSB for quantum 4 He confined in planar slits. Furthermore, this kind of asymmetric solutions were also found by Merkel and Löwen in open systems.…”
mentioning
confidence: 99%